Electrochemically Treated Pencil Graphite Electrodes Prepared in One Step for the Electrochemical Determination of Paracetamol - Koyun, O.; Gorduk, S.; Arvas, M. B.; Sahin, Y. (PLEIADES PUBLISHING LTD, 2018)
This article reports the electrochemical determination of paracetamol (PC) in the presence of ascorbic acid (AA) and caffeine (CF) using an electrochemically treated pencil graphite electrode. In this study, we describe the use of an electrode prepared by overoxidation between 0.0 and +2.1 V for paracetamol determination. The electrochemically treated pencil graphite electrodes (ETPGEs) were prepared using a cyclic voltammetric method. The electrode was characterized by Scanning Electron Microscopy (SEM), Electrochemical Impedance Spectroscopy (EIS), and Resonance Raman Spectroscopy. The differences in oxidation peak potentials were large enough to determine PC in the presence of AA and CF. The electroactive areas of the bare electrode and 10 scan-ETPGE in 0.5 M H2SO4 were calculated to be 0.0031 and 0.0341 cm(2), respectively. The sensor (10 scan-ETPGE in 0.5 M H2SO4) was sensitive to the PC with 1.74 x 10(-7) M limits of detection (S/N = 3). Finally, the developed method and the prepared electrodes were used for determination of PC in the pharmaceutical samples.
Keywords: paracetamol; modified pencil graphite electrode; overoxidized; sensor; pharmaceutical analysis; SIMULTANEOUS VOLTAMMETRIC DETERMINATION; GLASSY-CARBON ELECTRODE; ASCORBIC-ACID; PASTE ELECTRODE; URIC-ACID; PHARMACEUTICAL SAMPLES; ACETAMINOPHEN; CAFFEINE; DOPAMINE; Electrochemistry